WELFARE GRADE SOFT-SHELLED CRABS (Scylla cerrata) CULTIVATOR IN TANGKAHAN DURIAN VILLAGE, WEST BERANDAN SUBDISTRICT LANGKAT DISTRICT OF NORTH SUMATERA PROVINCE - Santy Pandiangan; Eni Yulinda; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on 17th May 2015 till 24th May 2015. The aim of this research is to describe the characteristic of soft-shelled crabs (Scylla cerrata) cultivator and analyzing the welfare level in the Tangkahan Durian Village, West Brandan Subdistrict, Langkat District of North Sumatera Province based on Badan Pusat Statistik 2005. The used method of this research is survey method and the determination of respondents by simple random sampling. The population of this research is the soft-shelled crabs (Scylla cerrata) cultivator. Remember about the homogeneity of cultivator population therefore sampling just from 30% respondents on just 9 peoples cultivator.The result of this research show the characteristic of soft-shelled crabs cultivator in the Tangkahan Durian Village, from 9 respondents only 77,78% belongs to productive categoryand 22,22% respondents belongs to very productive category, average of age 40 years old and the level of their education from 9 respondents there are 55,56% peoples finished their education in Junior High School and the others in Senior High School. Evenly, their burdening 5 peoples. Based on Badan Pusat Statistik 2005 the grade of welfare has been divided into three categories i.e. High Grade : score value 20-24, middle grade : score value 14-19, Low Grade : score value 8-13. Of assessed shoft-shelled cultivator in Kelurahan Tangkahan Durian belongs to middle welfare grade with score value 14-19.Kata Kunci : Welfare Grade, characteristic of soft-shelled crabs cultivator ,